Memperpanjang Umur Simpan Sayuran Sawi Putih Menggunakan Cairan Nutrisi - Ghufroni, Muhammad Afif; Warji, Warji; Amien, Elhamida Rezkia; Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2023)
Chinese Cabbage is a perishable commodity perishable because it has the characteristics of a living being and does not have the ability to sustain its life. In general, mustard greens are only stored in sacks. This method can cause damage to the mustard leaves and damage to other parts. Therefore the aim of this research is to analyze the freshness of the vegetables after they are harvested and given supply plant nutrients to extend the shelf life of vegetables. This study used a completely randomized design with 6 different treatments. In the first treatment (A) it was carried out with a box filled with clean water without nutrients. The second treatment (B) to the 5th treatment were sequentially added AB mix nutrition of 2 ml, 5 ml, 10 ml and 50 ml. Treatment 6 (F) was stored without water. Observations were made every 2 days for 6 days so that the total observation was 12 days and stored at room temperature. All treatments were repeated 3 times to obtain 18 experimental units. The results showed that the provision of 5 ml of nutrition had an effect on freshness as indicated by a low weight loss and root growth. Provision of more than 5 ml of nutrients in maintaining the freshness of the chinese cabbage has a bad impact because it causes rotting of the chinese cabbage. Keywords:  Chinese Cabbage, Effect, Freshness, Nutrition, Storage.